PENERAPAN TEKNOLOGI RFID, GSM DAN GPS PADA PERANCANGAN SISTEM KEAMANAN SEPEDA MOTOR - Agung Permana; Alex Surapati; Hendy Santosa (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
The theft and theft of motorbikes experienced a significant increase during the pandemic, which was 72.5%. The current motor vehicle security system only relies on keys for security, or uses additional security electronic devices such as alarms and security systems using touch sensors. However, this kind of safety does not guarantee that the motor is completely safe. The problem of this research is how to design a security system based on RFID, GSM and GPS. The purpose of this research is to design a motorcycle security system based on RFID, GSM and GPS that is able to monitor and secure motorcycles and to find out the difference in distance between GPS coordinates to facilitate the search for locations. The research method consists of hardware and software design and testing of the RFID system, GPS testing, GSM testing and overall flow testing. The test data show that the security system on a motorcycle using an RFID card is able to secure and detect without a plastic barrier as far as 3 cm while with a plastic barrier it can detect as far as 2.5, sending messages using SIM900A by sending commands to Arduino with a delay or delay. the time is about 3-5 seconds, and the GPS used has good accuracy by taking 8 coordinates or locations, the average difference is 4.5 m.